2015
DOI: 10.1089/mdr.2014.0265
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Antimicrobial Susceptibility ofActinobacillus pleuropneumoniaeIsolates in a Pig, Within a Batch of Pigs, and Among Batches of Pigs from One Farm

Abstract: Antimicrobial resistance in bacterial porcine respiratory pathogens has been shown to exist in many countries. However, little is known about the variability in antimicrobial susceptibility within a population of a single bacterial respiratory pathogen on a pig farm. This study examined the antimicrobial susceptibility of Actinobacillus pleuropneumoniae using multiple isolates within a pig and across the pigs in three different slaughter batches. Initially, the isolates from the three batches were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that whole‐genome sequencing can be used as predictor for App resistance to antimicrobial substances (Bossé, Li, Rogers, et al., ). In general, variation in levels of antimicrobial resistance of App isolates within the same herd can be high (Dayao et al., ), and there is not always an association between in vitro test results and success after treatment of disease.…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…It has been demonstrated that whole‐genome sequencing can be used as predictor for App resistance to antimicrobial substances (Bossé, Li, Rogers, et al., ). In general, variation in levels of antimicrobial resistance of App isolates within the same herd can be high (Dayao et al., ), and there is not always an association between in vitro test results and success after treatment of disease.…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…Antibacterial agents have been viewed as the first choice to treat the diseases caused by bacteria. However, the reported abuse and overuse of antibacterial agents is selecting for an ever-growing population of resistant pathogens, including APP [41][42][43][44]. The use of vaccines has proven to be a better choice in efforts to control PCP outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Canada five isolates demonstrated multidrug resistance to penicillins, streptomycin, tetracyclines and sulfanomides, whereas three others showed multiresistance to streptomycin, sulfonamides and tetracyclines (17). In many countries different levels resistance of A. pleuropneumoniae (10,14,25,30) have been determined. Bacterial pathogens that cause diseases in pigs including A. pleuropneumoniae often demonstrate resistance to drugs commonly used in veterinary practice.…”
Section: Methodsmentioning
confidence: 99%
“…A broad range of antimicrobial agents used for the treatment of disease including β-lactams (penicillin, amoxicillin, ampicillin, and ceftiofur), fluoroquinolones, gentamicin, trimethoprim/sulfamethoxazole, tiamulin, lincomycin/spectinomycin, and tetracyclines (25,30). Isolates of A. pleuropneumoniae are generally reported to be susceptible toward fluoroquinolones, ceftiofur and florfenicol, but various antimicrobial resistance patterns have been observed to others antimicrobials in different countries (10,32).…”
Section: Praca Oryginalnamentioning
confidence: 99%